Perilaku Shearwall Pelat Bergelombang Terhadap Beban Gempa Lateral Statik - Arya Rizki Darmawan; Sari Mayawati; Jumri Jumri (Lambung Mangkurat University Press, 2021)
Building portals with profile steel construction are very commonly used. However, with the potential for earthquakes in Indonesia which has a very large risk, the geometry of the portal must be given structural elements that can increase the lateral stiffness of the structure. One of the innovations to improve the lateral stiffness of the building portal is to provide a structural element in the form of a shearwall. Steel plate shearwall is one of the structural elements that serve to withstand lateral loads on a building, one of which is earthquake loads. Steel plate shearwall has a high slenderness rate. So that the lateral load will cause a large buckling problem in the shearwall plate. Corrugated steel plate is one of the innovations to solve the buckling problem. The purpose of this study was to analyze the effect of the wave plate shape on the shearwall. This research was conducted using numerical analysis using the ANSYS program to see thebehavior and strength of the steel plate shearwall. The shearwall models analyzed are beam-column frame type, shearwall with flat steel plate, and shearwall with corrugated steel plate, which is given a static lateral load at one end. This study shows that the yield load on the beam-column frame is 1400 kN, the shearwall for the flat steel plate is 1850 kN, and the shearwall for the corrugated steel plate is 2035 kN. The corrugated plate's geometric pattern obtained an increase in yield load of 9% compared to the flat plate. The buckling pattern that occurs in the flat plate shearwall and wave plate is diagonal shear buckling in the center area of the plate.